P-261 Creating an end of life care action alliance in southern staffordshire. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Hodges, Emma; Soulsby, Richard; Jones, Garry; Grant, Marianne
Abstract : Background: The Staffordshire Sustainability and Transformation Partnership (STP) prioritised end-of-life care but had no plan to engage with the Voluntary (VCSE) sector. Hospices span both the healthcare system and the VCSE sector. Whilst the statutory sector can be criticised for its fragmentation and lack of engagement, the VCSE sector is extremely amorphous and lacks coherence. Three hospices and the local voluntary sector infrastructure organisation organised two events to discuss end-of-life care with interested parties. Over fifteen organisations attended from large national charities to small local groups. These groups proposed creating a South Staffordshire End-of-Life Care Action Alliance. The STP and public health are engaging with the Alliance, whilst hospices provide a conduit between the Alliance and the STP's End-of-Life Care Board. Initial key areas of work included: Raising confidence in having end–of–life care related discussions across Alliance members; Creating a 'community of practice' to better connect members, reducing fragmentation, and creating a shared knowledge of community assets; Creating a bottom up, community development approach to care planning to demonstrate 'hard outcomes' can be achieved for the NHS. Financial support from an NHS England VCSE Accelerator project enabled the Alliance to fast track some outcomes and activities: Holding a conference of circa 100 people to explore a community development approach; Carrying out a training needs analysis; Delivering 'understanding loss' workshops in several localities; Training in Asset Based Community Development in end of life care; Holding a Network Mapping workshop; Holding numerous discussions with groups on care planning; Developing a 'brand' to launch the care planning project; Developing a user–led care planning pilot due to launch September: known as 'flipping care plans'. There is now in place a network of people within the VCSE community working together to improve end-of-life care. It is too early to determine the impact on the health system or delivery of tangible patient benefits, this is expected from the care planning pilot.